Enhancing Student Learning in Tourism Program through a Technology-Based Constructive Learning Model: The Case of Universitas Ciputra - Lucky Cahyana Subadi; Ellen Lawrencia Yahya; Hilda Yunita Wono; Lexi Pranata Budidharmanto; Karina Enny Agustina (UNUSA Press, 2023)
Indonesia’s age demographic bonus increases in 2021, it indicates a positive signal towards the higher proportion of productive age which has implications for increasing competitiveness and bargaining power of the Indonesian people. Since the Covid-19 pandemic, technology has been widely used in the teaching and learning process. As an effort to improve the learning process, support from several aspects is needed, one of the important things is the learning model itself. The virtual face-to-face learning model (Online) adopted in this study includes 4 stages (4P) namely Pembukaan (opening), Pendalaman (deepening), Penerapan (application), and Perenungan (reflection), supported by the use of technology in teaching and learning activities. This study aims to determine the effectiveness of the learning process using the 4P learning model, and the use of technology in improving knowledge, skills, and attitudes in the student learning process. The research method was implemented through limited trials on 2 subjects: Risk Management and Sustainable Tourism Management, by adapting the classroom action research model. While the data analysis used in this research is descriptive analysis. From the research, it was found that there was an increase in students' pre-test and post-test scores for two courses, this concluded that the 4P learning model succeeded in increasing student competence and could be applied in various courses at different times.